2020
DOI: 10.3390/molecules25061403
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Inositol Pyrophosphate Biosynthetic Enzymes in Metabolic Diseases

Abstract: In mammals, a family of three inositol hexakisphosphate kinases (IP6Ks) synthesizes the inositol pyrophosphate 5-IP7 from IP6. Genetic deletion of Ip6k1 protects mice from high fat diet induced obesity, insulin resistance and fatty liver. IP6K1 generated 5-IP7 promotes insulin secretion from pancreatic β-cells, whereas it reduces insulin signaling in metabolic tissues by inhibiting the protein kinase Akt. Thus, IP6K1 promotes high fat diet induced hyperinsulinemia and insulin resistance in mice while its delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 270 publications
0
31
0
Order By: Relevance
“…In addition, pharmacological inhibition of IP6K by the IP6K inhibitor TNP [N2-(m-trifluorobenzyl), N6-(p-nitrobenzyl)purine] increases AMPK phosphorylation and AMPK signaling events in the adipocytes of high-fat-diet-fed mice [59]. More detailed perspectives on the IP6K-mediated control of metabolic homeostasis by IP6Ks have been reviewed [64].…”
Section: Metabolic Homeostasismentioning
confidence: 99%
“…In addition, pharmacological inhibition of IP6K by the IP6K inhibitor TNP [N2-(m-trifluorobenzyl), N6-(p-nitrobenzyl)purine] increases AMPK phosphorylation and AMPK signaling events in the adipocytes of high-fat-diet-fed mice [59]. More detailed perspectives on the IP6K-mediated control of metabolic homeostasis by IP6Ks have been reviewed [64].…”
Section: Metabolic Homeostasismentioning
confidence: 99%
“…These important features rely on the di(β)phosphate group to enable competition of these molecules with phosphatidylinositol-3,4,5-trisphosphate (PIP 3 ) in order to bind to pleckestrin homology domains (PH) [ 27 ]. In mammals, generation of knockout mouse models has established the in vivo impacts and significance of IPs pathways [ 28 ], while pharmacological modulation of inositol and its pyrophosphate-related pathways have proved to be beneficial in several pathological settings [ 29 , 30 , 31 ].…”
Section: Inositol Pyrophosphatesmentioning
confidence: 99%
“…The four common forms of inositol pyrophosphates found in nature are 5-diphosphoinositol (1,3,4,6)-tetrakisphosphate(5PP-IP4), 1-diphosphoinositol (2,3,4,5,6) pentakisphosphate (1PP-IP5 or 1-IP7), 5-diphosphoinositol (1,2,3,4,6) pentakisphosphate (5PP-IP5 or 5-IP7) and 1,5-bisdiphosphoinositol (2,3,4,6) tetrakisphosphate (1,5PP2-IP4 or 1,5-IP8) [19]. The synthesis of 5PP-IP5 occurs by the conversion of IP6 by the enzyme inositol hexakisphosphate kinase 1 (IP6K1) [14,15].…”
Section: Scyllo-inositol Muco-inositol D-chiro-inositol L-chiro-inosimentioning
confidence: 99%
“…The effects of inositol phosphates and IP6Ks have long been considered for a target of obesity and metabolic diseases [19]. Many experiments in mice revealed that IP6K knockout displayed reduced body weight, fat accumulation, and percentage of fat mass as well as increased percentage of lean body mass [21,81], suggesting the role of inositol pyrophosphates on obesity.…”
Section: Inositol Phosphates On Obesity and Metabolic Parametersmentioning
confidence: 99%